The effect of individual personality of the big five model and the non physical work environment on employee performance in PT Bank Syariah Mandiri in Pontianak - Miftahuljannah, Miftahuljannah (JURNAL MANAJEMEN MOTIVASI, 2018)
The purpose of this study was to investigate the influence ofindividual personalitiesand the big five model of non-physical work environment on the performance ofindependent syriah bank employee in London. In this study the authors used aresearch method is descriptive and Verifikatif, where descriptive studies that describethe real state of the object contained in the study required data obtained from the fillingof questionnaires, interviews, observation, and study documentation. Verifikatif isbasically wanted to test the truth of the hypothesis which is carried out through fielddata collection. The research was conducted on 69 employees in branch offices, BankSyariah Mandiri in Pontianak, to support research to ensure compliance with theobjectives to be achieved then the respondent will answer in the form of crosstabulation tabulated and analyzed and the conclusions drawn. The method used isdescriptive analysis, causal and associative multiple linear regression analysis.The results of this study concluded that by looking at the variable Big Five PersonalityModel and Non-Physical Work Environment jointly or simultaneously have a positiveand significant impact on the creation of employee performance at PT. Bank SyariahMandiri Pontianak. The most dominant variable affecting the creation of employeeperformance at PT. Bank Syariah Mandiri Pontianak is:Non-Physical WorkEnvironment variables.